COABRA: collaborative secured auditing with privacy preservation policy on group shared data in cloud based digital repositories - S, Arunkumar; M.S, Anbarasi (International Journal of Engineering and Technology, 2019)
Cloud storage services like digital repositories, allow users to store and share data across multiple users within a group. However it is always a big time challenge to conserve the integrity of the data stored, due to the high probability of inevitable hardware and software failures. The Third Party Auditor (TPA) is allowed to verify the integrity of the data ie checking correctness of the data. There are many challenges during auditing process, mainly privacy issue. Another prevailing challenge is to achieve high degree of access control and traceability along with extensive abstraction to preserve privacy.This proposal provides solution for this privacy preserving issue by Holomorphic Circle Sign (HCS) method without revealing the identity of signer where the signer is one of the group members. Also provides Random Combination Block (RCB) method to audit random combination of encoded data rather than actual data. RCB method provides reduced data transmission and avoids decoding/recalculation process.The proposal also support public auditing on regenerated data which is used for providing reliability on shared data and prompt traceability mechanism that tracks.Â